Work Ability and Psychosocial Factors in Healthcare Settings During COVID-19 Pandemic – Specific Focus on Ageing Workers - Kurashvili Mari; Reinhold Karin; Järvis Marina (Economics and Business)
The paper aims to find out what kind of impact socio-demographic and psychosocial factors have on the work ability among healthcare workers during COVID-19 pandemic – specific focus on ageing workers. Work Ability Index (WAI) and the short version of the Copenhagen Psychosocial Questionnaire (COPSOQ-III) were used to analyse the impact. 424 healthcare workers from Georgian and Estonian hospitals (including doctors and nurses) answered the questionnaires. On average, the sample had a good work ability, with 48.8 % viewing it as good and 29.3 % as excellent in Georgia, and 53.6 % of participants had a good and 15.4 % excellent work ability in Estonia. The COPSOQ showed critical values in the scales of “work pace” and “emotional demands”. These results were expected as the data were collected during the pandemic period. “Sleep troubles”, “burnout”, “depressive symptoms”, and “insecurity over working conditions” were the risk factors more likely associated with ageing (+55) health workers than younger ones. The scales “quantitative demands”, “work pace”, “job insecurity”, “burnout”, “stress”, “sleep troubles”, “offensive behaviours” and “depressive symptoms” were in negative correlation with WAI. The results show that the work ability is higher when these factors are lower. The scales “role clarity”, “recognition”, “sense of community at work”, “quality of leadership”, “organisational justice”, “self-efficacy”, “meaning of work”, “job satisfaction” and “possibilities for development” were the risk factors in positive correlation with WAI, thus acting as work ability preservative aspects.